Non-controlling large shareholders in emerging markets: Evidence from China - Cheng, Minying; Lin, Bingxuan; Lu, Rui; Wei, Minghai (Journal of Corporate Finance, 2020)
Non-controlling large shareholders play an important role in corporate governance in emerging markets where controlling shareholder expropriation is a major concern. We argue that non-controlling large shareholders are faced with two non-conflicting incentives: to take advantage of their information advantage and obtain positive abnormal returns when they trade company shares, and to serve as effective monitors and minimize controlling shareholders' appropriation of company wealth. Using a sample of large shareholders' selling events upon the expiration of the lockup period following the split-share structure reform in China, we find that non-controlling large shareholders successfully time the market, as shown by their positive abnormal returns when selling their shares. Their returns are higher if they have a greater information advantage. Furthermore, the positive returns of the controlling large shareholder are negatively related to non-controlling large shareholders' ownership, suggesting that non-controlling large shareholders play a monitoring role and prevent controlling shareholders from looting the company. We also show that large shareholders affiliated with the controlling shareholders are not subject to as high a level of monitoring as those controlling shareholders are. Furthermore, both firm opaqueness and the severity of agency cost affect the quality of non-controlling large shareholders' monitoring.